(untitled) (Bangladesh Journal of Neuroscience, 2019)
Focal Cortical Dysplasia (FCD) is one of the most common causes of refractory epilepsy in children as well as adult where malformed cortical development occurs resulting from abnormal neuronal migration due to both genetic and acquired factors. Herein, a 22-year-old male presented with recurrent secondary generalized tonic seizure with aura since childhood. Despite adequate anti-epileptic medications with good compliance the seizure was uncontrolled. As a cause, Type II FCD was diagnosed by specific neuroimaging findings supported by EEG abnormalities. Till now in refractory epilepsy FCD is rarely diagnosed but there remains a good hope of cure by surgical intervention. Bangladesh Journal of Neuroscience 2019; Vol. 35 (1): 46-50